Cognitive Reactivity: Cultural Adaptation and Psychometric Testing of the Persian Version of the Leiden Index of Depression Sensitivity Revised (LEIDS-R) in an Iranian Sample - Ostovar, Shahla; Md Nor, Mariani; Griffiths, Mark D.; Chermahini, Soghra Akbari (Springer Verlag (Germany), 2017)
Cognitive reactivity (CR) to the experimental induction of sad mood has been found to predict relapse in recovered depressed patients. The Leiden Index of Depression Sensitivity Revised (LEIDS-R) is a self-report measure of CR. The aim of the present study was to establish the validity and reliability of the Persian version of the LEIDS-R. The participants were recovered depressed and non-depressed Iranian individuals (n = 833). The analyses included content validation, factor analysis, construct validity, and reliability testing. Preliminary construct validation analysis confirmed that factor analysis was appropriate for the Persian version of the LEIDS-R. Factor analysis displayed similar factor loadings to the original English version. The total internal consistency of the translated version, which was assessed using Cronbach’s alpha coefficient, was equal to 0.90. The test-retest reliability of the total score was equal to that of the test-retest conducted after a two-week interval at 0.94. Content validity, face validity, and construct validity, as well as reliability analysis were all found to be satisfactory for the Persian version of the LEIDS-R. The Persian version of the LEIDS-R appears to be valid and reliable for use in future studies, and has properties comparable to the original version and to that obtained in previous studies.